Análisis in vitro de la microdureza superficial del esmalte dental humano expuesto a dos agentes blanqueadores y sometido a la acción del fluoruro de sodio - Miranda Viteri, María Victoria (2017)
ABSTRACT The research objective was the effect on the surface microhardness of human dental enamel exposed to two bleaching agents and subjected to the action of sodium fluoride. Two bleaching agents were employed; 35% hydrogen peroxide and 35% carbamide peroxide. 25 agents were used by the bleaching agent, taking into account the inclusion and exclusion criteria. Subsequently using a low speed handpiece these teeth were separated from the root crown which used a carbide disc, and the sound was given a finished type on each surface. Each enamel fragment was placed in a ring made of plastic tube with 2.0 cm in diameter incorporating a self-curing polyester resin, called a probe. Each enamel fragment was then exposed to the bleaching agent based on 35% carbamide peroxide (Opalescence Ultradent) for 30 minutes; and 35% hydrogen (Whiteness HP Maxx-FGM) for 45 minutes respectively. The microhardness was measured using a Leco Model LMV-50V Durometer, with a load of 20gf. Then the same specimens were immersed in 2% sodium fluoride solution for a period of 4 minutes and then immersed in artificial saliva for 21 h and 56 min. After being removed from the solution of the artificial saliva, washed with distilled water for one minute and dried with gauze, samples were taken to the Leco micro-meter model LMV-50V, using a load of 20gf with a time of 5 seconds in the Measurement of the Knoop Line. The results obtained showed a highly significant difference (p <0.001) in the surface microhardness between hydrogen peroxide and carbamide peroxide, the decrease of microhardness being the mayor with carbamide peroxide. In addition, the average surface microhardness decreased with both agents compared to the initial microhardness. After being subjected to sodium fluoride it was observed that the average microhardness of the premolars that were subjected to carbamide peroxide increased.